Hubungan Antara Konformitas dengan Kecenderungan Perilaku Kenakalan Remaja - Suharti, Rena Greosty; , Dr. Eny Purwandari, M.Si (2016)
This study aims to determine: the relationship between conformity with the trends in the behavior of juvenile delinquency and the contribution of effective conformity to delinquency remaja.Hipotesis proposed in this study is that there is a positive relationship between conformity with the trends in the behavior of juvenile delinquency. Subjects in this study were high school students Christian Purwodadi, which numbered 120 students and SMA Negeri 1 Purwodadi, totaling 120 students. The sampling technique used was cluster random. Methods of data collection using a scale of conformity and the scale of juvenile delinquency behavior tendencies. Data were analyzed using product moment correlation. Based on analysis of product moment obtained no significant positive relationship between conformity with the trend of juvenile delinquency. It is shown that the results of conformity scale high category and the results of the scale of behavioral tendency of juvenile delinquency also high category. And the effective contribution of the variable conformity with the tendency of juvenile delinquency behavior 54,5% there are other factors that influence.